Carboxymethyl Cellulose Grafted on Mesoporous Cobalt Oxide Milieu: Synthesis, Formation Mechanism and Electrochemical Features. Issue 10 (8th March 2022) - Inbamani, Manohara Babu; Dass, Arockia Jency; Inbamani, Rathinamala
Abstract: In the present study, mesoporous Cox Oy /C nanoflakes were fabricated using facile one‐pot short span hydrothermal approach to explore its potential in energy storage devices. The fabricated composite electrode delivers maximum specific capacity of 372 C g −1 at a current density of 1 A g −1 with a meager charge transfer resistance (1.5 Ω). The excellent energy storage property is attributed to the presence of hierarchical arrangement of inter connected flaky structure that provides a fresh lanes for the mobilization of electrolyte ions. Moreover, an asymmetric supercapacitor (ASC) was assembled by sandwiching battery‐type Faradic electrode and carbonaceous electrode. The device shows excellent electrochemical capability and noble cycling stability (90.9 % capacitance retention) after 10000 cycles of charge/discharge. Such enduring prominent properties of the fabricated device will make a benchmark in real time applications. Abstract : A simple and facile hydrothermal approach was adopted to fabricate mesoporous carboxymethyl cellulose grafted cobalt oxide nanocomposite for energy storage applications. The electrochemical performance of the as‐prepared electrodes was checked in three/two electrode cell in aqueous alkaline medium. Especially, Co3 O4 /C electrode delivers a specific capacity of 372 C g −1 (three electrode configuration). Ultra‐high energy/power was achieved in two terminal mode and it could be attributed to unique morphology of the fabricated electrodes that provides pathways for ion transportation.